(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Antepartum hemorrhage complicates 2-5% of pregnancies, whichapproximately one-third are due to placenta previa. Placenta previa is acondition derived to an abnormal implantation of the embryos in thelower uterine segment. In placenta previa hemorrhage is more likely to occur during third trimester,as a consequence of the development of the lower uterine segment and of the dilation of the cervix due to the uterine contractions; alsovaginal examination may lead to an antepartum hemorrhage. Risk factors for the development of placenta previa include prior cesarean delivery, pregnancy termination, intrauterine surgery, smoking, multifetal gestation, increasing parity, maternal age and the rising rates of Cesarean section. Placenta previa is associated with adverse consequences for both mother and children, such as Intra-Uterine Growth Restriction (IUGR), preterm birth, antenatal and intra-partum hemorrhage, maternal blood transfusion and emergency hysterectomy. Placenta previa has been diagnosed increasingly in recent decades, due to mostly to the widespread use of ultrasound (US). Apart from ultrasound a valid imaging modality to study and investigate placenta in antepartum period seems to be magnetic resonance (MR).Careful monitoring of high risk pregnancies is of utmost importance. Avoidance of unnecessary caesarean sections and early week’s pregnancy terminations can minimize the placenta previa. In diagnosed cases, preoperative planning, preoperative decisions and good postoperative management can safe a mother and child. J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 26-30